Analysis of risk factors faced by Chinese international students based on fuzzy comprehensive evaluation model - Gao, Junhong; Zhao, Zhiyu; Li, Hongwei (Frontiers in Education, 2024)
IntroductionChina has contributed the most international students to the global higher-education sector for over a decade. Existing research has indicated various risk factors faced by international students. However, few studies have examined the risks experienced by Chinese international students. Two research questions were investigated in this study: (1) Which risk factor has the greatest impact on Chinese international students when studying abroad? and (2) Which risk factor is most frequently experienced by Chinese international students when studying abroad?MethodTo address these questions, this study proposes a fuzzy comprehensive evaluation model for evaluating the risk factors faced by Chinese international students. The model comprises six second-level factors and 22 third-level indicators, which was empirically examined by data collected through 556 questionnaires. The analytical hierarchy process and factor analysis were employed to calculate the index weight of second-level factors and third-level indicators.ResultsThe results reveal that the risk factor, psychological discrepancy, has the greatest impact and is most likely to be experienced by Chinese international students. The paper provides an integrated research perspective to study the risk of international students.DiscussionThe paper discussed the factors that impact the risk faced by Chinese international students. The risk faced by Chinese international students was found to be high. Psychological discrepancy, academic choice, and cross-cultural adaptation were the three risk factors that were most likely to be experienced by Chinese international students. Psychological discrepancy, barriers to study, and unforeseen incidents had the highest impact on total risk. Therefore, attention should be paid to these risk factors to avoid the occurrence of risk and its negative impacts.